2003
DOI: 10.1292/jvms.65.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-Hydroxydopamine on the Development of the Immune System in Chickens.

Abstract: ABSTRACT. It has been suggested that the sympathetic nervous system communicates with lymphocytes expressing cell surface receptors for neurotransmitters such as norepinephrine (NE), on the basis of the finding that neurotransmitters modify immune responses in mammalian species. We confirmed that chicken lymphocytes in the brusa of Fabricius, thymus and spleen expressed β-adrenergic receptor (β-AR) mRNA from embryonic day (E) 10 and that intracellular cAMP level was elevated by NE, suggesting that lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
13

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
3
0
13
Order By: Relevance
“…The nervous system might influence the bursal biology releasing active neurotransmitters and neuropeptides from the nerve terminals innervating the bursa that act on lymphocytes or non-lymphoid cells expressing receptors for these molecules (Ali et al, 1996;Motobu et al, 2003;Ricci et al, 1996;. Nevertheless, the changes in the innervation or in the expression of neurotransmitter receptors during the involution of the bursa of Fabricius have not been analyzed in detail.…”
Section: Bursa Of Fabriciusmentioning
confidence: 99%
“…The nervous system might influence the bursal biology releasing active neurotransmitters and neuropeptides from the nerve terminals innervating the bursa that act on lymphocytes or non-lymphoid cells expressing receptors for these molecules (Ali et al, 1996;Motobu et al, 2003;Ricci et al, 1996;. Nevertheless, the changes in the innervation or in the expression of neurotransmitter receptors during the involution of the bursa of Fabricius have not been analyzed in detail.…”
Section: Bursa Of Fabriciusmentioning
confidence: 99%
“…Using autoradiography, this group also showed that the majority of the ␤ 2 -adrenergic receptors are localized in the medullar compartment of the thymus, an observation consistent with a maturation-dependent regulation of ␤ -expression in thymocytes [22,23] . Expression of ␤ -adrenergic receptors in thymocytes has also been demonstrated in other species, including chicken [24] . In most of these studies and in others not included here, it has been shown that these receptors are functional, by evaluating, for example, classical effects of ␤ -stimulation such as increases in cAMP levels following exposure of thymic cells to the appropriate agonists.…”
Section: Adrenergic Receptors In the Thymusmentioning
confidence: 84%
“…Easy access to the developing chicken embryo facilitates short-term analysis following pulsed xenobiotic exposure (Hamilton & Bloom, 1984;Dietert et al, 1985;Fox & Grasman, 1999;Grasman & Whitacre, 2001;Motobu et al, 2003). E12 lead exposure in female chickens suppresses not only Th1-dependent function but also the capacity of thymocytes to produce (ex vivo) Th1 cytokines regardless of whether they are cocultured with lead-exposed or control thymic stroma (Lee & Dietert, 2003).…”
mentioning
confidence: 99%